OOCYTE COLLECTION TECHNIQUES IN THE DROMEDARY CAMEL - Tinson, A. H.; McKinnon, O.; Singh, K.; Kuhad, K. S.; Sambyal, R. (Emirates Journal of Food and Agriculture, 2017)
Please see the scanned pdf version in full text